Relationships between festive theater and the theory of Dramatic Genres of Luisa Josefina Hernández (The Voz a Vos Bulletin, 2024)
The festivities, the theater and the stage area source of immense scenic wealth inMexico. The so-called festivitiespopular have been presented since the time ofthe Colony and later in MexicoIndependent, producing complexinteractions between native cultures,European cultures, culturesAfro-descendants in addition to thosecome from the cultural industry of the centuryXIX and XX century, resulting in adynamic cultural mix that conforms tothe heritage of the so-called Popular Art.The festive theater, the street scene, theMexican professional theater likeliving and moving traditionsadapt, mix, and transmute into oneenriched scene. When the oldritual is desacralized it tends to becometheater normally inclined to the genre ofthe farce, whose mechanisms can beinterpret and explain through theoryof dramatic genres of the playwright,Mexican teacher and theorist Luisa JosefinaHernández, with her study of farce,seeking to contribute to clarifying thesecharacteristics and operationthrough type or simple characters, toneholiday and replacement mechanism orsymbolic to produce catharsisfarsic.